2020
DOI: 10.1097/rmr.0000000000000259
|View full text |Cite
|
Sign up to set email alerts
|

MRI of Emergent Intracranial Infections and Their Complications

Abstract: Acute intracranial infections of the central nervous system and skull base are uncommon but time sensitive diagnoses that may present to the emergency department. As symptoms are frequently nonspecific or lack typical features of an infectious process, a high index of suspicion is required to confidently make the diagnosis, and imaging may not only serve as the first clue to an intracranial infection, but is often necessary to completely characterize the disease process and exclude any confounding conditions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…is suggests that CSF routine and biochemical tests can go some way to diagnosing intracranial infections. Nevertheless, as intracranial infections have many causes, the main common ones being bacterial, viral, and tuberculosis infections [12,13], this study further analyzed the markers of infection in the CSF of patients after brain tumour surgery. e results found that the levels of PCT, HBP, and MMP-9 in the CSF of those with intracranial infection were significantly higher than those of without infection.…”
Section: Discussionmentioning
confidence: 99%
“…is suggests that CSF routine and biochemical tests can go some way to diagnosing intracranial infections. Nevertheless, as intracranial infections have many causes, the main common ones being bacterial, viral, and tuberculosis infections [12,13], this study further analyzed the markers of infection in the CSF of patients after brain tumour surgery. e results found that the levels of PCT, HBP, and MMP-9 in the CSF of those with intracranial infection were significantly higher than those of without infection.…”
Section: Discussionmentioning
confidence: 99%